The Chemical Ecology Approach to Reveal Fungal Metabolites for Arthropod Pest Management - Berestetskiy, Alexander (Microorganisms, 2021)
Biorational insecticides (for instance, avermectins, spinosins, azadirachtin, and afidopyropen) of natural origin are increasingly being used in agriculture. The review considers the chemical ecology approach for the search for new compounds with insecticidal properties (entomotoxic, antifeedant, and hormonal) produced by fungi of various ecological groups (entomopathogens, soil saprotrophs, endophytes, phytopathogens, and mushrooms). The literature survey revealed that insecticidal metabolites of entomopathogenic fungi have not been sufficiently studied, and most of the well-characterized compounds show moderate insecticidal activity. The greatest number of substances with insecticidal properties was found to be produced by soil fungi, mainly from the genera Aspergillus and Penicillium. Metabolites with insecticidal and antifeedant properties were also found in endophytic and phytopathogenic fungi. It was noted that insect pests of stored products are mostly low sensitive to mycotoxins. Mushrooms were found to be promising producers of antifeedant compounds as well as insecticidal proteins. The expansion of the number of substances with insecticidal properties detected in prospective fungal species is possible by mining fungal genomes for secondary metabolite gene clusters and secreted proteins with their subsequent activation by various methods. The efficacy of these studies can be increased with high-throughput techniques of extraction of fungal metabolites and their analysis by various methods of chromatography and mass spectrometry.